An Initial Assessment of Effects of Seafloor Roughnesson Coherent Sound Reflection from the Seafloor - Jones, A.; Duncan, Alexander; Maggi, Amos (Australian Acoustical Society, 2013)
A roughened seafloor may be expected to scatter incident sound at non-specular angles, but also to reflect coherently at the specular angle, with some loss of amplitude attributed to the scattering and some loss attributed to sound transmission into, and absorption within, the seafloor. Our initial expectation was that a reasonable estimation of the total coherent reflection loss, at a given grazing angle, might be obtained simply from a combination of the loss attributed to a flat seafloor based on its geoacoustic properties, and the separate coherent loss due to the roughness scattering described for a pressure release surface. To test this hypothesis, loss values obtained using this simple additionof model outputs were produced for several seafloor material types with prescribed roughness profiles. These results are compared with loss values obtained using the perturbation approach for rough surface scattering from stratified media described by Kuperman and Schmidt (JASA, 86, Oct. 1989). The latter is a model which describes the coherent plane wave reflection from a rough surface of stratified material which has specified geoacoustic properties.